Impact of Ramadan Diurnal Intermittent Fasting on Hypoglycemic Events in Patients With Type 2 Diabetes: A Systematic Review of Randomized Controlled Trials and Observational Studies - Abdelrahim, Dana; Faris, MoezAlIslam E.; Hassanein, Mohamed; Shakir, Ayman Z.; Yusuf, Ayesha M.; Almeneessier, Aljohara S.; BaHammam, Ahmed S. (Frontiers in Endocrinology, 2021)
Ramadan is the ninth month of the lunar calendar, during which Muslims abstain from predawn to sunset for thirty consecutive days. Ramadan fasting is observed by all healthy Muslim adults as well as a large population of type 2 diabetic Muslims. Hypoglycemic events (HE) have been looked at as one of the most serious complications associated with diabetes management and is associated with increased cardiovascular disease risk. Conflicting results have been reported concerning the incidence of HE among subjects with Type 2 diabetes (T2DM) observing Ramadan fasting. This review aims to summarize the available scientific evidence on the occurrence of HE, and the effects of variable moderators on the incidence of HE among patients with T2DM during Ramadan. A systematic review of available observational studies and randomized controlled studies (RCT) for patients with T2DM who fasted during Ramadan was conducted, and HE was reported as the primary outcome. Ten databases were searched from the date of database inception in 1950 to the end of October 2020 for relevant studies. Sixty-eight studies, 35 RCTs, and 33 observational studies each met the inclusion criteria. Non-sulfonylureas hypoglycemic medications showed superior effects in lowering the incidence of HE over the sulfonylureas ones. Variable moderators such as sex, geographical location, body anthropometric, season, dietary behaviors, fasting duration, time since diagnosis, and pre-fasting education were associated with experiencing HE during Ramadan in both observational studies well as RCTs.